2009
DOI: 10.1093/rheumatology/kep250
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic features of the hand and wrist in systemic sclerosis

Abstract: Our study depicts the main sonographic abnormalities of the SSc hand. Using US, we found an unexpectedly high prevalence of joint pathology in SSc without clinically involved hands. The clinical usefulness of US in the assessment of SSc articular involvement either in clinical practice or in therapeutic trials is yet to be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
67
3
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 23 publications
12
67
3
4
Order By: Relevance
“…A grade 2 or 3 power Doppler signal was more likely observed in RA patients compared to grade 1 in SSc patients which indicates the articular difference between the two groups. This coincides with the results of studies carried out by other authors [36][37][38]. In RA patients we found a significant correlation between US detected synovitis and the DAS28, ESR and CRP.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A grade 2 or 3 power Doppler signal was more likely observed in RA patients compared to grade 1 in SSc patients which indicates the articular difference between the two groups. This coincides with the results of studies carried out by other authors [36][37][38]. In RA patients we found a significant correlation between US detected synovitis and the DAS28, ESR and CRP.…”
Section: Discussionsupporting
confidence: 92%
“…Again, this coincides with the results of other authors [41] who stated that US tenosynovitis findings in scleroderma do not correlate with disability and they explained that by their patients having mildly severe tendon affection as suggested by the low prevalence of tendon friction rub. This unique pattern specific to scleroderma patients may be an important way to suspect scleroderma in cases of diffuse or uncertain articular manifestations where clinical examination may be insufficient in detecting articular involvement [36,38,42]. Regarding US of soft tissues, calcifications were detected in both scleroderma and RA patients (10% and 6.6%) respectively, with no statistically significant pattern, these data are in accordance with previous studies that showed calcifications in SSc patients in about 10-50% of the patients [43].…”
Section: Discussionmentioning
confidence: 99%
“…As the authors noted, skeletal hand involvement is underestimated in SSc, thus supporting the potential role of US in the assessment of hand involvement in SSc. The data provided by Elhai et al are in agreement with previous reports (2)(3)(4) showing the complementary role of US in assessing the broad spectrum of hand conditions in SSc patients, particularly synovitis and tenosynovitis.…”
Section: Assessment Of Hand Involvement In Systemic Sclerosis By Ultrsupporting
confidence: 87%
“…The diagnosis of hand involvement is primarily based on clinical signs and symptoms, and radiographic abnormalities [1e6]. Nevertheless, a recent study has emphasized the role of ultrasonography (US) in identifying subclinical synovitis or tenosynovitis that cannot be detected by means of radiography [7].…”
mentioning
confidence: 99%